2004
DOI: 10.1002/ps.939
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of spinosad against the western flower thrips, Frankliniella occidentalis, and its impact on associated biological control agents on greenhouse cucumbers in southern Ontario

Abstract: Insecticides are the most commonly used tactic to control western flower thrips (WFT), Frankliniella occidentalis Pergande (Thysanoptera: Thripidae), on greenhouse cucumber. However, WFT has developed resistance to several of the insecticides presently in use. In addition, some of these insecticides adversely affect greenhouse biological control agents used to control WFT, resulting in subsequent pest resurgence. Therefore, there is a need to identify novel insecticides with unique modes of action for use in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 11 publications
2
48
1
9
Order By: Relevance
“…Spinosad was effective against adult and larval F. occidentalis in Trials 1 and 4, and it has been widely reported as effective against F. occidentalis in other countries (Funderburk et al 2000;Reitz et al 2003;Jones et al 2005). Spinosad is registered for use against F. occidentalis in Australia.…”
Section: Discussionmentioning
confidence: 96%
“…Spinosad was effective against adult and larval F. occidentalis in Trials 1 and 4, and it has been widely reported as effective against F. occidentalis in other countries (Funderburk et al 2000;Reitz et al 2003;Jones et al 2005). Spinosad is registered for use against F. occidentalis in Australia.…”
Section: Discussionmentioning
confidence: 96%
“…The assessment of WFT susceptibility to formetanate, methamidophos, dimethoate, and spinosad indicated that WFT had the highest susceptibility to spinosad (Vargas & Ubillo 2005). In 2005, it was found that spinosad is an effective insecticide to control the immature and mature stages of WFT in cucumber greenhouses (Jones et al 2005). Broughton and Herron (2007) showed that increasing the rate of abamectin and The results showed that lufenuron, abamectin, and fipronil caused maximum mortality in two days after application.…”
Section: Biology and Problems Concerning Frankliniella Occidentalismentioning
confidence: 99%
“…It has been proved that spinosad has no detrimental impact on natural enemies of F. occidentalis. Therefore, spinosad is a convenient and safe tool in combination with some natural enemies of WFT and it is one of the keys to conservation of Orius species (Eger et al 1998;Jones et al 2005). Unfortunately, a certain level of resistance to spinosad has been documented, therefore spinosad should be completely avoided in areas where the resistance has developed (Demirozer et al 2012).…”
Section: Biology and Problems Concerning Frankliniella Occidentalismentioning
confidence: 99%
“…habitat destruction, oviposition, resting, 44 mating sites) (Desneux et al 2007). Therefore, it is important to develop new reduced-risk 45 insecticides to use in Integrated Pest Management (IPM) programs with minimal impact on 46 beneficial arthropods (Jones et al 2005). In this regard, spinosad is known to be effective against T. diseases and weeds were controlled using products recommended for onion production 92 (pendimethanil, ioxynil, metalaxyl-M + copper, dimethomorph + pyraclostrobin, cyprodinil + 93 fludioxonil).…”
Section: Introduction 34mentioning
confidence: 99%